Shore erosion between Arboletes and Punta San Bernardo, caribbean coast of Colombia (2007)
The present morphology and the inventory of the historical shoreline changes (1938-2005) between Arboletes and Punta San Bernardo evidenced a strong erosional trend along 160 of its 180lan tota1-1ength, resulting in the disparition/retreat of numerous beaches, followed by the consequent flooding/erosion of the adjacent littoral terraces and mangrove swamps. In general terms, the littoral Arbo1etes-Punta San Bernardo retreated 30 to 100m during the last seven decades, at rates between 0.5 and 1.5 m/year; maximum values were found at some critical sectors in the Arboletes-Punta Brava shore segment where magnitudes of coastline retreat were in the order of 900-1.500m at erosion rates up to 70 m/year during the period 19601975. Shore erosion in the study area results both from marine and subaerial processes and the combination of geological factors (neotectonism and effects of mud diapirism, minor stocks of sands, relative sea level rise, poor geotechnical characteristics of cliff's rocks) and human interventions (intensive sand mining from beaches and rivers, land uses with inadequate water management practices, adverse effects of groins and other rigid structures of defense). The precise definition of each one of these factors is necessary for planning the development of the area considering the future sea level rise associated to the Global Climate Change.